(untitled) (Communication & Society, 2014)
Based on a comparative analysis of celebrity magazines in Portugal and Brazil, this article analyses the representation of children of celebrities. Those magazines privilege an extreme personalisation of the stories and a strong valuation of the photographic image, representing children as a source of happiness and affection within the family. Nonetheless, drawing on celebrity studies and on children’s rights and their implications for journalism, we concluded that this positive representation frequently collides with the children’s rights to privacy, to be protected from public embarrassment and to be heard in the issues that affect them.